Minimum inhibitory concentrations and antibiotic resistant genes in the freshwater cyanobacteria Planktothirx agardhii - Dias, Elsa (2017)
Objectives: Cyanobacteria are ubiquitous prokaryotes in aquatic ecosystems and although they can be exposed to antibiotics and antibiotic resistant bacteria, their role on water resistome was never investigated. Planktothrix agardhii is one of the most common cyanobacteria species in Portuguese freshwater reservoirs, often exhibition long residence time in those reservoirs. This work aimed to evaluate the antibiotic susceptibility patterns and resistance mechanisms in P. agardhii in order to assess their putative contribution to the global pool of resistance determinants in freshwater. Methods: We investigated 8 strains of P. agardhii, previously isolated from different freshwater reservoirs. The antibiotic susceptibility was evaluated by a microdilution method previously adapted for cyanobacteria, against beta-lactams, aminoglycosides, quinolones, trimethoprim and tetracycline. Minimum inhibitory concentrations (MIC) were determined according to cell density (DO, 450nm) and microscopic examination of cultures integrity. All strains were searched for antibiotic resistance genes and class 1, 2 and 3 integrons by PCR/sequencing. Results: The results showed that P. agardhii is not susceptible to trimethoprim and quinolones within the tested concentrations (0.0015-1.6 mg/L). However, the cell growth is strongly inhibited by amoxicillin (median MIC value of 0.1mg/L). The other antibiotics presented the following median MICs: ceftazidime, 1.6 mg/L; ceftriaxone, 0.8 mg/L; tetracycline, 0.4 mg/L; kanamycine, 0.2 mg/L and gentamicine, 0.1mg/L. None of the P. agardhii strains exhibited genes associated with trimethoprim and quinolones resistance, which suggests that these cyanobacteria are intrinsically non susceptible to this antibiotics. Conversely, genes associated with streptomycin (strAstrB) and sulfonamide (sul1) resistance, as well as a 1-type integron, were detected in three of the strains. These strains were isolated from the freshwater reservoirs where Planktothrix blooms are frequent and. This suggests that the presence of a common antibiotic resistant determinant in P. agardhii might be a result from a similar selective pressure within those reservoirs. Conclusions: The presence of antibiotic resistance genes and integrons, as well as the reduced susceptibility to antibiotics, suggest that cyanobacteria may play a role on freshwater resistome and eventually contribute to the dissemination of antibiotic resistance in freshwater environments.